Hopes and realities : closing the gap between women's aspirations and their reproductive experiences - The Alan Guttmacher Institute (New York, N.Y., 1995)
A guide to the report--The basic conditions of women's lives--Starting sexual relationships: marriage and living together--Family size: hopes and realities--Planning pregnancy and protecting reproductive health--Narrowing the gap.
Incluye gráficos.
Keywords: SEXO; SALUD DE LA MUJER; REPRODUCCIÓN; SALUD REPRODUCTIVA